Young Children With Behavior Disorders in Low-Income Families: The Role of Clinic Observations in the Assessment of Parenting. Issue 3 (2nd October 2017) - Peisch, Virginia; Lafko Breslend, Nicole; Jones, Deborah J.; MacFarlane, Mary; Forehand, Rex
ABSTRACT: Children from low-income families are at elevated risk of meeting diagnostic criteria for behavior disorders. Although mastery-based behavioral parent training (BPT) programs have a robust evidence base for reducing disruptive behaviors of young children, socioeconomically disadvantaged families are more likely to drop out of treatment and, in turn, are less likely to benefit. Therefore, efficient assessment and treatment may be needed. Less research, however, has addressed the value of time-consuming behavioral observations relative to caregiver-report of problem behaviors in the assessment of this at-risk and underserved group. In the current study, 43 low-income parents and their clinic-referred child were observed during a standard mastery-based BPT interaction task (Child's Game) at baseline. Findings revealed that parents were observed to display an extremely high proportion of maladaptive behaviors targeted for reduction by subsequent treatment (Instructions plus Questions) relative to behaviors that the treatment was designed to increase (Attends plus Rewards). In contrast, parents reported they utilized relatively high and low rates of positive and negative parenting, respectively. Behaviorally observed parenting was not correlated with caregiver-reported parenting. The findings suggest that baseline observations of behaviors targeted in mastery-based BPT interventions are an important part of assessment in parenting programs for low-income families with young disruptive children.